Tobacco cessation intervention for pregnant women in Argentina and Uruguay: study protocol - Althabe, Fernando (2013)
BACKGROUND: Argentina and Uruguay are among the countries with the highest proportion of pregnant women who smoke. The implementation of an effective smoking cessation intervention would have a significant impact on the health of mothers and infants. The "5 A´s" (Ask, Advise, Assess, Assist, Arrange) is a strategy consisting of a brief cessation counseling session of 5-15 minutes delivered by a trained provider. The "5 A´s" is considered the standard of care worldwide; however, it is under used in Argentina and Uruguay. METHODS: We will conduct a two-arm, parallel cluster randomized controlled trial of an implementation intervention in 20 prenatal care settings in Argentina and Uruguay. Prenatal care settings will be randomly allocated to either an intervention or a control group after a baseline data collection period. Midwives´ facilitators in the 10 intervention prenatal clinics (clusters) will be identified and trained to deliver the "5 A´s" to pregnant women and will then disseminate and implement the program. The 10 clusters in the control group will continue with their standard in-service activities. The intervention will be tailored by formative research to be readily applicable to local prenatal care services at maternity hospitals and acceptable to local pregnant women and health providers. Our primary hypothesis is that the intervention is feasible in prenatal clinics in Argentina and Uruguay and will increase the frequency of women receiving tobacco use cessation counseling during pregnancy in the intervention clinics compared to the control clinics. Our secondary hypotheses are that the intervention will decrease the frequency of women who smoke by the end of pregnancy, and that the intervention will increase the attitudes and readiness of midwives towards providing counseling to women in the intervention clinics compared to the control clinics.